Mewujudkan Impian Orang Tua: Makna Birrul Walidain dalam Iklan Rumah Wakaf Indonesia (Jurnal Kopis: Kajian Penelitian dan Pemikiran Komunikasi Penyiaran Islam, 2024)
Birrul Walidain is a concept in Islam that emphasizes the importance of filial piety. Through Rumah Wakaf Indonesia's advertisement "Apa Hadiah Paling Beharga Untuk Orang Tua" holds values and meanings of goodness in the aspect of filial piety. This research aims to reveal the meaning of Birrul Walidain through the signs contained in the Rumah Wakaf Indonesia advertisement using Roland Barthes semiotics, namely the denotation, connotation and myth stages. This study found that there are three scopes of the meaning of Birrul Walidain, namely obeying the orders of both parents, honoring both parents and helping both parents. As a result, the connotation meaning of obeying the orders of both parents includes commitment to achieving dreams and realizing the dreams of his late mother. The myth is that filial piety can bring abundant sustenance. The connotation meaning of honoring parents includes giving attention and affection with the myth of giving all attention and always not to defer to parents. Finally, the connotation meaning of helping parents includes establishing a good relationship by helping parents' needs. The myth of helping parents is a lifelong commitment to honor and give attention to parents.